PENGARUH INVESTASI LANGSUNG ASING, INVESTASI PORTOFOLIO DAN NILAI TUKAR RUPIAH TERHADAP PERKEMBANGAN INDUSTRI PERBANKAN DI INDONESIA TAHUN 2015-2024. - Kamar, Karnawi; Kusuma Wardhani, Annisa Risqi Sulistya; Chyrine, Ervana (LPPM UNIVERSITAS INSAN PEMBANGUNAN INDONESIA, 2026)
This study aims to analyze the effect of Foreign Direct Investment (FDI), Portfolio Investment, and Rupiah Exchange Rate on the development of the banking industry in Indonesia during the period 2015–2024. The object of this research is the Indonesian banking industry, which is influenced by foreign capital inflows and exchange rate fluctuations. The data used in this study are secondary data from the Central Bank of Indonesia, the Financial Services Authority (OJK), and other relevant institutions. The analytical technique applied is multiple linear regression to examine both partial and simultaneous effects of the independent variables. The results indicate that Foreign Direct Investment, Portfolio Investment, and the Rupiah Exchange Rate jointly have a significant impact on the development of the banking industry, while partially, each variable shows a varied level of influence.